An Example for the Construction of Masculinity in Turkey: The Woman Has No Name - Sebnem, Cansun (European Scientific Journal, ESJ, 2017)
In Turkey, the academic works on gender rather focus on Womenâ€™s Studies, whilst Masculinity Studies are perceived as a relatively new research field. From this perspective, the aim of this work is to look closely at the social construction of masculinity in Turkey through the feminist author Duygu Asenaâ€™s book entitled KadÄ±nÄ±n adÄ± yok (The woman has no name). This book hit the bookstores in 1987 and had a selling record in Turkey with its forty editions within year. Duygu Asena rather depicts her male characters from a critical perspective. According to her, in the social construction of masculinity in Turkey we see that men use psychological, physical and sexual violence against women. Men criticize women, limit their liberties, beat them at times, have physical intercourse with them without necessarily asking for their consent. Even though in Turkey masculinity is actually getting modernized and we see non-traditional forms of masculinity around, we notice that hegemonic masculinity is getting reproduced in homosocial communities. We can argue that men encounter insecurity in the midst of the modernization process and suffer from the oppression related to the â€œmale rolesâ€. We recommend that there ought to be more contributions on Masculinity Studies in Turkey.